Factors governing tumor penetration of nanomedicines: intrinsic and extrinsic determinants - Shin, Dongwon; Choi, Jiwoong; Park, Byeongmin; Kim, Sun Hwa; Shim, Man Kyu (Royal Society of Chemistry, 2026)
Nanomedicine-based drug delivery has shown considerable promise for cancer therapy; however, the efficient transport and deep penetration of nanoparticles within solid tumors remain major challenges for clinical translation. These limitations arise from the combined effects of nanoparticle physicochemical properties and biological transport barriers acting across multiple biological scales, rather than being governed by any single isolated parameter. Accordingly, nanoparticle transport and tumor penetration cannot be adequately understood by considering individual parameters in isolation, but instead reflect the combined contributions of intrinsic determinants related to nanoparticle properties and extrinsic determinants associated with penetration-enhancing interventions, underscoring the need for an integrated framework that explicitly distinguishes and organizes these two classes of factors when evaluating nanoparticle transport in vivo. In this review, we provide a structured overview of the intrinsic and extrinsic determinants that regulate nanoparticle transport in vivo. First, we summarize intrinsic nanoparticle-related factors and discuss how their physicochemical properties influence key transport processes, including systemic circulation, tumor accumulation and penetration, cellular uptake, and excretion. Second, we review advanced engineering strategies designed to enhance tissue penetration, such as size- and charge-transformable nanoplatforms that aim to balance prolonged circulation with improved intratumoral distribution. Third, we outline extrinsic intervention-based approaches, including external stimuli and pharmacological modulators, that improve nanoparticle penetration by modulating transport barriers within solid tumors. Finally, we discuss remaining challenges and knowledge gaps that limit the predictability and reproducibility of nanoparticle transport in vivo, and provide perspectives on how a systems-level understanding of these interdependent factors can support the clinical translation of nanomedicines.